Audit Sistem Informasi Movable Fixed Asset dan Inventory Management dengan Framework Cobit5 - Eva zuraidah; Besus Maula Sulthon (STMIK Budi Darma, 2023)
Companies for their daily activities use Office applications such as Word and Excel for bookkeeping, they switch to Movable Fixed Asset and Inventory Management applications because they often lose data when there is a sudden power failure. The purpose of this Audit is to find out how much the effectiveness and efficiency of the Movable Fixed Asset and Inventory Applications are used in the Company. Benefits for PT. Semesta's work is to evaluate whether they are using the Movable Fixed Asset and Inventory Applications correctly. COBIT is a framework that is often used by auditors, especially information systems auditors. COBIT can be used as a comprehensive tool to create information technology governance in a company. The results of the study were carried out to measure the performance of the application in the form of analysis, level of capability mapping, and recommendations for the company. The standards used in research are COBIT 5 focusing on the EDM, APO, BAI, DSS, and MEA.PT domains. Karya Semesta With the Cobit 5 Framework, a conclusion can be drawn based on the deployment of the questionnaire, there is the highest value in the domain EDM04 Ensure Resource Optimization has a gap of 0.38 with Ti Managed and Measurable capabilities and APO12 has a gap of 0.33, DSS5 has a gap of 0.28 with the P level or Partially achieved in its entirety, while for the APO10 maturity level it is smaller, namely 2.67, it has not reached the target level, then GAP will occur -0.33 and also BAI09 maturity is smaller than the target level, a gap of -0.23 will occur, and MEA01 the maturity level is also below the target level L or Largely achieved, with IT capabilities in the Defined Process for those that are still below the target level must be increased again so that the company is better